PEMBELAJARAN POKOK BAHASAN HUKUM GRAVITASI DI MADRASAH BERDASARKAN ABDURRAHMAN AL-KHAZINI - Santi, Santi; Darajat, Siti Zakiah Annasir (Universitas Islam Negeri Raden Fatah Palembang, 2017)
This paper aims to reveal the law of gravity that triggered western scientist (Sir Isaac Newton) with Islamic scientists. This finding is expected to be a medium of learning IPA Madrasah Aliyah in teaching materials that will be used. Data collection is done by qualitative method that is with approach of history of philosophy of science with Islamic perspective. Data analysis is done qualitatively by connecting each aspect covering the rationale, the similarity of language, the concepts used, the influence of other figures, the year of glory and the study of other literature. From all the process of analysis that has been done and the discussion that has been exposed it can be concluded that Sir Isaac newton in the thought of the law of gravity has been influenced by al-khazini. These findings can be taught in Madrasahs through lecture, demonstration and other methods that are sociologically anthropologically close to madrasah culture.